2000
DOI: 10.1088/0953-8984/12/26/318
|View full text |Cite
|
Sign up to set email alerts
|

The tricritical point in the quantum IsingS= 1 spin glass with biaxial crystal-field effects

Abstract: We study a quantum generalization of the infinite-range Sherrington-Kirkpatrick spin-glass model with biaxial crystal-field effects described by two uniaxial anisotropy parameters Dx and Dy. For spin dimensionality S = 1 we report an analytical and numerical analysis in the (T, Dx, Dy) parameter space (with T being the temperature). For D ≡ Dx = Dy the model effectively becomes classical and identical with the crystal-field-split spin-glass Ising model (introduced by Ghatak and Sherrington) showing a discontin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…where 'biaxial crystal-field effects' 'D x and D y ' are 'two uniaxial anisotropy parameters' describing 'biaxial crystal-field effects' [88]. Note that in [88] the forms DS z 2 ÀD(S x 2 ÀS y 2 )+DS(S+1) and D P 2 have also been invoked.…”
Section: Model Magnetic Spin Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…where 'biaxial crystal-field effects' 'D x and D y ' are 'two uniaxial anisotropy parameters' describing 'biaxial crystal-field effects' [88]. Note that in [88] the forms DS z 2 ÀD(S x 2 ÀS y 2 )+DS(S+1) and D P 2 have also been invoked.…”
Section: Model Magnetic Spin Systemsmentioning
confidence: 99%
“…Note that in [88] the forms DS z 2 ÀD(S x 2 ÀS y 2 )+DS(S+1) and D P 2 have also been invoked. The quote [88]: 'for DD x ¼ D y the model effectively becomes classical and identical with the crystal-field-split spin-glass Ising model' is pertinent for our discussion. (iii) Spin-S Ising model with 'transverse crystal field'…”
Section: Model Magnetic Spin Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TCP in the quantum anisotropic spin-1 glass Ising model has been investigated. 57 They showed that the disordered model possesses unusual features, manifesting both continuous and first-order phase transitions. This shows that the role of the biaxial crystal field is very important.…”
Section: Introductionmentioning
confidence: 99%